Wetting Behavior and Support Interactions in Imidazolium-Based Supported Ionic Liquid Phase Materials-A Systematic Study by Solid-State Nuclear Magnetic Resonance Spectroscopy - Frosch, Matthias; Tavera Méndez, Cindy Ly; Koch, Angela Barbara; Schörner, Markus; Haumann, Marco; Hartmann, Martin; Wisser, Dorothea (Journal of Physical Chemistry C, 2023)
Supported ionic liquid phase (SILP) catalysts are an extremely promising class of materials that combine advantageous concepts from both homogeneous and heterogeneous catalysis. Optimized SILP catalysts should exhibit a thin, homogeneous, and continuous film of the ionic liquid (IL) to avoid pore blocking and to ensure a good accessibility of the catalyst. Yet, the interactions between the IL and the support, which determine the formation of such a film, are still poorly understood. We investigate here in a systematic way the deposition of three imidazolium-based ILs on silica supports with different surface areas and morphologies using 1H magic angle spinning solid-state nuclear magnetic resonance spectroscopy. We demonstrate that the point of complete surface wetting can be determined by the disappearance of the 1H resonance of isolated silanol groups and that this point depends both on the textural properties of the support material and the chemical properties of the IL.1H chemical shifts also provide valuable insight into hydrogen bonding interactions within the IL and between the IL and the support. They indicate cleavage of the anion-cation hydrogen bonds upon IL deposition and the formation of new hydrogen bonds with the silica surface.
CRIS-Team WoS Importer:2023-05-26